2022
DOI: 10.2147/prbm.s357301
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Infertility Care Services and Emotional Health of South Asian Women

Abstract: Background Treatment tolerability and treatment environment are two major spheres of infertility care that may associate with women’s emotional health and coping mechanisms. Aim The present study aimed at assessing the relationship between infertility treatment quality and various aspects of emotion-focus coping, problem-focus coping, and avoidance coping mechanisms. Method The study was completed by using standardized tools and data from thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…Our results align with previous findings in other cultures worldwide. 24,38,39 Infertile couples frequently experience tremendous isolation from the fertile world due to perceived or actual social rejection and a lack of understanding from relatives and friends regarding their extreme desperation. 30 The current study showed that infertile couples living in an extended family type, especially those who do not have relatives suffering from infertility have higher global stress scores, have significantly higher psychological distress, and less evaluation of their general health than the nuclear family type.…”
Section: Methodsmentioning
confidence: 99%
“…Our results align with previous findings in other cultures worldwide. 24,38,39 Infertile couples frequently experience tremendous isolation from the fertile world due to perceived or actual social rejection and a lack of understanding from relatives and friends regarding their extreme desperation. 30 The current study showed that infertile couples living in an extended family type, especially those who do not have relatives suffering from infertility have higher global stress scores, have significantly higher psychological distress, and less evaluation of their general health than the nuclear family type.…”
Section: Methodsmentioning
confidence: 99%
“…1 Some known causes of infertility include aging, oxidative stress (OS), environmental factors, certain lifestyles, and hormones. 1 Hyperglycemia is one of the conditions that can cause OS, which affects the ovarian and testicular cell activity. Reactive oxygen species (ROS), an inevitable byproduct of glucose metabolism, causes OS.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS), an inevitable byproduct of glucose metabolism, causes OS. 1 Excessive production of ROS leads to DNA damage and the activation of poly-ADP-ribose polymerase1 a (PARP1) pathway, which is seen in hyperglycemia. 2,3 PARP1 inhibits the activity of glyceraldehyde-3phosphate dehydrogenase, which leads to the accumulation of glyceraldehyde-3-phosphate (GA3P) and other intermediates of glycolysis, such as fructose-6-phosphate and glucose-6p.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations